HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KEPUASAN KLIEN INSTALASI GAWAT DARURAT RUMAH SAKIT ELISABETH MEDAN TAHUN 2018 - Samfriati Sinurat; Lilis Novitarum; Iman Bahagia Halawa (Elisabeth Health Jurnal, 2018)
Emergency Installation (IGD) is one of the main lines of help to clients. Therapeutic communication is required in dealing with clients with emergency situations. Therapeutic communication is the most important factor used to establish therapeutic relationships between nurses and clients.Goals : The purposed of this research to analyze therapeutic communication relationship of nurse with client satisfaction at IGD RS Santa Elisabeth Medan.Methods: This study used a cross-sectional approach with accidental sampling technique of 94 respondents.Result : Based on Fisher's Exact Test with p value = 0,018 <0,05 meaning there is significant relation between therapeutic communication of nurse with Client satisfaction at Emergency Installation of Santa Elisabeth Medan Hospital.Conlcution : To improve the excellent service to clients, it is expected that nurses will apply therapeutic communication and improve their skills to communicate by attending training or seminars.